2010
DOI: 10.1016/j.semarthrit.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Epidemiology and Progression of Systemic Lupus Erythematosus

Abstract: Objectives-This review examines the burden and patterns of disease in systemic lupus erythematosus (SLE) and the influence and interactions of gender, ethnicity, age, and psychosocial attributes with respect to disease progression, focusing on issues relevant to clinical practice and research. Methods-PubMed literature search complemented by review of bibliographies listed in identified articles.Results-An increased risk among reproductive age women is clearly seen in African Americans in the United States. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
533
5
34

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(596 citation statements)
references
References 104 publications
24
533
5
34
Order By: Relevance
“…The prevalence and incidence of RA were the highest, followed by SLE and Sjö gren's syndrome, and the rates for Behçet's disease were the lowest. The findings on the incidence of RA and SLE in the present study are similar to those reported in previous studies (13,14). There are notable differences in the sex distribution among ARDs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence and incidence of RA were the highest, followed by SLE and Sjö gren's syndrome, and the rates for Behçet's disease were the lowest. The findings on the incidence of RA and SLE in the present study are similar to those reported in previous studies (13,14). There are notable differences in the sex distribution among ARDs.…”
Section: Discussionsupporting
confidence: 91%
“…The reported prevalence of SLE in the population is 20 -150 cases per 100,000 cases across a broad diversity of geographic regions (1,14). In a recent comprehensive review, the incidence rates of SLE ranged from approximately 1-10 per 100,000 person-years, and the prevalence generally ranged from 20 -70 per 100,000 person-years (14,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…SLE is more prevalent in women, affecting females of childbearing age in 80 -90% of cases (4). In addition to sex discrepancies, SLE is 2-4 times more frequent and more severe among African Americans and other nonwhite populations (5,6). The clinical expression of SLE also varies by ethnicity; Hispanic, African American, and Asian SLE patients tend to have more hematologic, neurologic, and renal disease manifestations (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sex discrepancies, SLE is 2-4 times more frequent and more severe among African Americans and other nonwhite populations (5,6). The clinical expression of SLE also varies by ethnicity; Hispanic, African American, and Asian SLE patients tend to have more hematologic, neurologic, and renal disease manifestations (5). These patients also experience more organ damage over time and at a faster rate than white patients, regardless of age and sex (5).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of SLE almost always employs immunomodulatory therapies that suppress this autoimmune response. Immunosuppressive drugs, such as cyclophosphamide and mycophenolate mofetil (MMF), reduce tissue inflammation and injury, and the mortality for patients with SLE has improved in recent decades 2, 3 .…”
Section: Introductionmentioning
confidence: 99%